Peran Investasi Modal Manusia dan Modal Fisik dalam Meningkatkan Pertumbuhan Produktivitas Tenaga Kerja di Indonesia - Riske Yuliana Hutami; Novya Zulva Riani (Ecosains: Jurnal Ilmiah Ekonomi dan Pembangunan, 2022)
This study aims to analyze; (1) the effect of human capital investment which includes education (primary education, secondary education, tertiary education) and health variables on labor productivity growth in Indonesia (2) the effect of physical capital investment as proxied by Gross Fixed Capital Formation (PMTB) on labor productivity growth  in Indonesia (3) the effect of human capital investment and physical capital investment on labor productivity growth in Indonesia. The data used is secondary data from 34 provinces in Indonesia in 2016-2020 obtained from related institutions. This study uses panel data regression with the Common Effect Model approach. The results show that (1) human capital investment which includes education variables (primary education, secondary education, tertiary education) and health, each has a positive and significant effect on labor productivity growth in Indonesia (2) physical capital investment as a proxy for Gross Fixed Capital Formation (PMTB) has a negative and insignificant effect on labor productivity growth in Indonesia (3) investment in human capital and physical capital together has a significant effect on labor productivity growth in Indonesia